Solitary pulmonary nodule: A diagnostic algorithm in the light of current imaging technique - Khan, Ali Nawaz; Al-Jahdali, Hamdan H; Irion, Klaus L; Arabi, Mohammad; Koteyar, Shyam Sunder (Avicenna Journal of Medicine, 2011)
The solitary pulmonary nodule (SPN) is frequently seen on chest radiographs and computed tomography (CT). The finding of a SPN usually provokes a flurry of clinical and imaging activity as an SPN in at-risk population is an alert signal of possible lung cancer. The frequency of malignant nodules in a given population is variable and depends on the endemicity of granulomatous disease. The percentage of malignant nodules also rises when dealing with at-risk population. The problem is compounded by the fact that with the present generation of CT scanners, 1-2 mm nodules are discovered in approximately half of the smokers aged 50 years or older scanned. A variety of management approaches are applied in the work-up of SPN often requiring evaluation over a long period of time to establish a benign or malignant diagnosis. Comparison with previous imaging studies and morphologic evaluation of the size, margins, and internal characteristics are usually the first step in the evaluation of these nodules. It is often necessary to use additional imaging techniques and occasionally invasive procedures such a percutaneous needle lung or a surgical biopsy. Until recently, the guidelines for follow-up of indeterminate noncalcified nodules detected on nonscreening CT was a minimum of 2 years. However, during the past few years due to further refinements in CT technology and better understanding of tumor behavior, it has prompted a revision of the guidelines of the follow-up of small indeterminate nodules. These guidelines have been endorsed by the Fleischner Society.
Keywords: Benign lung nodules; CT; lung cancer; PET/CT; pulmonary nodules